"Next Day" Examination Reduces Radiation Exposure in Cervical Spine Clearance at a Level 1 Pediatric Trauma Center: Preliminary Findings. Issue 5 (May 2019) - Kavuri, Venkat; Pannu, Gurpal; Moront, Matthew; Pizzutillo, Peter; Herman, Martin
Abstract : Background: Safe and effective clearance of the pediatric cervical spine presents a challenging problem due to a myriad of reasons, which has often led to further imaging studies such as computed tomographic (CT) scans being performed, exposing the pediatric patient to significant radiation with a potential increased cancer risk. The goal of this study is to develop an effective algorithm for cervical spine clearance that minimizes radiation exposure. Methods: A cervical spine clearance protocol had been utilized in our institution from 2002 to 2011. In October 2012, the protocol was revised to provide indications for appropriate imaging by utilizing repeat "next day" physical examination. In 2014, the protocol was again revised with the desired goal of decreasing the use of CT scans through increased involvement of the Spine Service. A retrospective review was commenced using information from the Trauma Database from 2011 to 2014. Three groups were analyzed according to which protocol the patients were evaluated under: 2011, 2012, and 2014 protocols. Results: During the study period, 762 patients underwent cervical spine clearance; 259 (2011 protocol), 360 (2012 protocol), and 143 (2014 protocol). The average age of all patients was 8.8 years, with 28% of patients younger than 5 years of age. There were no missed or delayed diagnoses of cervical spine injury. The use of CT scans decreased during the study period from 90% (2011 protocol) to 42% (2012 protocol) to 28.7% (2014 protocol). There was an increase in time to removal of the cervical collar at 13 to 24 hours from 8% (2011 protocol) to 22% (2012 protocol) to 19% (2014 protocol). This was not associated with an increase in hospital length of stay, which averaged 2.51 days (2011 protocol), 2.45 days (2012 protocol), and 2.27 days (2014 protocol). Conclusions: Repeat "next day" clinical examinations and increased involvement of the Spine Service decreased radiation exposure without compromising the diagnosis of cervical spine injury or increasing the length of stay at a Level One Pediatric Trauma Center in this pilot study. Level of Evidence: Level 4—case series. Abstract : Supplemental Digital Content is available in the text.